Investigating factors associated with raised blood pressure in New Zealand school children : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - David Roldan, Maria (Massey University, 2019)
Background: Childhood hypertension is associated with an increased risk of target organ damage and adulthood hypertension. Over the last few years, the prevalence of paediatric primary hypertension has been growing. A better understanding of the risk factors associated with high blood pressure could facilitate early detection and intervention. To date, no studies in New Zealand have investigated high blood pressure in the paediatric population. Aim: The aim of this study was to investigate risk factors for raised blood pressure in year five and six primary school children, living in Auckland, New Zealand. Methods: We examined cross-sectional data for school children participating in The Children’s Bone Study. Anthropometric measures included weight, height, BMI, waist circumference and percent body fat. Blood pressure was measured on a single occasion, and the average of three readings was used for analysis. Elevated blood pressure and hypertension were defined according to the American Academy of Pediatrics’ criteria. Demographic information was collected using a questionnaire. Logistic regressions were used to examine the associations between gender, ethnicity and obesity with raised blood pressure (≥90th percentile). Results: The proportion of children (n=669, 10.4 ± 0.62 years) with elevated and hypertensive blood pressure readings were 14.3% and 31.1%, respectively. Age and gender were not significantly associated with raised blood pressure (p=0.485; p=0.109, respectively). South Asian children had significantly greater odds of presenting with raised blood pressure compared to European (OR: 1.65, 95% CI: 1.02—2.65, p<0.05). The adjusted odds of screening with raised blood pressure were significantly greater for children with an obese (OR: 2.88, 95% CI: 1.65—5.01, p<0.001) and overweight (OR: 2.43, 95% CI: 1.54—3.84, p<0.001) BMI than non-overweight children. Percent body fat above the normal range (OR: 2.16, 95% CI:1.51— 3.09, p<0.001) and a waist-to-height ratio ≥0.5 (OR: 2.60, 95% CI: 1.60—4.22, p<0.001) were associated with increased odds of raised blood pressure readings, irrespective of age, gender and ethnicity. Conclusion: Ethnicity, and general and central obesity appear to be key risk factors for raised blood pressure in children. Although blood pressure was only measured on a single occasion, the results suggest that paediatric hypertension may be a potential health concern for New Zealand. Further research is needed to establish a more accurate picture of the situation and allow for New Zealand specific guidelines to be formulated.
Figure 2.1 re-used with publisher's permission.
Keywords: Hypertension in children; Risk factors; Health surveys; New Zealand; Auckland